An Empirical Study of Service Quality and Customer Satisfaction of Malaysian Air Passenger - Halim Mahphoth, M; Koe, W-L; Krishnan, R; Erfani Abd Ghani, A; Ismail, S (KnE Social Sciences, 2018)
The vast majority of Malaysian air passenger have competitive choices among airlines and different service options. Customer satisfaction is what guarantees the survival of airlines and it is achievable only by matching the passengers needs with the services. Assessment of service quality and its subsequent management is of utmost importance for them to be competitive and successful in this industry. Thus, the purpose of this study was set to determine the relationship between service quality (SERVQUAL) and customer satisfaction of Malaysian air passenger. An adopted SERVQUAL instrument including five service quality constructs: empathy, tangibles, responsiveness, reliability and assurance were employed to measure the passengers perceptions about the service quality of airlines. Data were collected from 187 respondents using convenience sampling. The outcome of multiple regression analysis showed that responsiveness, reliability and assurance have a positive significant impact on customer satisfaction. However, empathy and tangible variables recorded an insignificant relationship with customer satisfaction. Conclusion and recommendation were discussed. Keywords: service quality, customer satisfaction, air passenger